Notarial mediation in the accounting practices of medieval powers (13th-14th centuries): an overview (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
In recent years, many studies have been dedicated to the accounting documentation of the medieval period and to the role played by notaries as producers of records. However, the crucial function that notaries engaged with the accounting management of the late medieval political powers has been neglected. Starting from a large-scale comparison between cases documented for South-eastern France and Northern Italy, and also taking into account a variety of documents produced by secular and ecclesiastical institutional subjects, this essay analyses the occurrence and specific contents of notarial mediation in the unfolding of documentary accounting practices.
Keywords: Northern Italy; Provence; Savoy; Dauphiné; Notaries; Accounting; Middle Ages